Investigation of long-term change in web-based data traffic in terms of performance evaluation - ÇİLİNGİRTÜRK, AHMET METE (My University, 2022)
Çalışma, web sitelerinin tıklama verilerinden elde edilen sayfa merkezli verilerin dağılımlarını modellemeyi amaçlamaktadır. Bu modelleme sayesinde simülasyon ve planlama modelleri için kaynak oluşturulması amaçlanmaktadır. Çevrimiçi pazarlama davranışlarının anlaşılmasında web sitelerinin kullanımı ve göstergelerinin analizi oldukça önemlidir. İş hedefleri doğrultusunda hazır giyim ve aksesuarların pazarlandığı e-ticaret ve bilgi edinme ve yayma amaçlı haber siteleri hedef olarak belirlenmiş web siteleridir. İlgili web sitelerinin hemen çıkma oranı, sayfa görüntüleme ve kalış süresi göstergelerinin dağılımları incelenmiştir. Elde edilen dağılım bilgileri ile özel sektörde kullanılan satış simülasyonları başta olmak üzere web siteleri arası performans değerlendirme gibi çeşitli alanlarda kullanılabileceği düşünülmektedir.

In this study, the development levels of Developing 8 countries were tried to be concretized in line with the growth-centered, humancentered and environment-centered development approach and criteria. From 1997 to the present, Bangladesh, Nigeria and Pakistan have arisen from the low-income group to the lower-middle-income group, Indonesia and Iran form the lower-middle-income group to the uppermiddle income group. Lower-middle income Egypt, Malaysia and Turkey have continued to stay in the upper-middle income groups. Between 1997-2018 the share of industrial production in total value-added Indonesia, Iran, Malaysia, Nigeria and Turkey have decreased. It remained stable in Egypt and increased in Bangladesh and Pakistan. The share of manufacturing production in total value added follows a similar course to industrial productions. Between 1997 and 2018, D-8 countries except Nigeria managed to raise their human development levels to the next level. Bangladesh and Pakistan have been promoted from low human development level to medium human development. Egypt, Indonesia and Iran were able to move from medium human development level to high human development level. Malaysia has risen from a high level of human development to a very high level of human development. Meanwhile, Turkey was able to jump very high human development levels from medium human development level. It observed that the performance of D-8 countries in realizing the United Nations Sustainable Development Objectives varies between 50% and 70%. Iran, Malaysia and Turkey, for the moment, is located above the middle of sustainable development league. Egypt is right in the middle, Indonesia, Bangladesh, Pakistan and Nigeria are located below in the middle. It seen that Malaysia takes the first place among D-8 countries in terms of development of financial institutions and financial development course between 1997 and 2018, it is observed that the financial development index value shows a steady increase trends in countries other than Egypt, Indonesia and Pakistan.
Keywords: Simülasyon Modelleri; Web Sitesi İstatistikleri; İstatistiksel Dağılımlar; İnternet Kullanım Davranışı; Uzun Vadeli Değişim; Simulation Models; Website Statistics; Statistical Distributions; Internet Usage Behavior; Long Term Change